ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN INFERTILITAS DI POLI KANDUNGAN RS PKT SIAGA RAMANIA TAHUN 2018 - Lisa Septiana (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2018)
Background: Female infertility is one of the most important issues for public health. According to the World Health Organization, the incidence of infertile cases are increasing each year. Likewise, according to the Central Bureau of Statistics, infertile incidence in Indonesia has been increasing. Pupuk Kaltim Siaga Ramania Hospital is one of the hospitals in East Kalimantan Province with improving number for visiting infertile patients. This study aimed to analyze the factors related to the incidence of infertility. Subjects and Method: The design of this study is cross-sectional. The study was conducted at Poly obstetric Pupuk Kaltim Siaga Ramania Hospital from January to March, 2018. A sample of 180 fertile women with sampling through purposive sampling technique. The dependent variable was infertility. The independent variables were age, obesity, long married, and employment status on the incidence of infertility. The data were collected by medical records and questionnaires. Data were analyzed with Chi Square statistical analysis with significance level of 0.05.Results: Female infertility was affected by age (p=0.000, X2 count= 18,037), obesity (OR=3.360; CI 95%=1.773-6.367; p<0.000; X2 count = 13.155), long married (OR=4.972; CI 95%=2.525-9.790; p<0.000; X2 count = 21.670), dan employment status (OR=2.764; CI 95%=1.478-5.171; p<0.002; X2 count = 9.401). Conclusion: It can be concluded that there is correlation of age, obesity, long married, and employment status on the incidence of infertility. It is necessary for improving the knowledge regarding risk factors and for couples who had obesity to applied a pattern of a healthy diet by keeping weight ideally. Keywords                    : age, obesity, long married, employment and infertilityBibliography   :  26 (2007-2017)